Discriminatory Practices Against Sellers by the Shopee Marketplace from the Perspective of Law Number 5 of 1999 and the Principle of Al-‘Ad?lah According to Sayyid Qutb - Salma Salsabila; Mustapa Khamal Rokan (IHSA Institute, 2026)
This study examines the practice of seller discrimination by the Shopee marketplace, which emerges through algorithmic policies, paid promotional services, and platform features that tend to favor certain sellers. This issue is analyzed based on Law No.?5 of 1999 concerning the Prohibition of Monopolistic Practices and Unfair Business Competition, as well as the principle of justice in Islamic economics, which emphasizes distributive fairness and balance in commercial transactions (muamalah). This research employs a normative juridical with a constitutional and philosophical approach to identify the impact of such approach discrimination on small and medium-sized enterprises (SMEs) that operate as sellers on the Shopee platform. The findings show that the existence of paid promotions, store rankings, and Shopee’s algorithmic recommendations potentially leads to unfair business competition, as these systems prioritize sellers who can afford to pay more for greater visibility. This directly weakens the position of smaller sellers, limits their market access, and creates disparities that contradict the principles of justice in Islamic economics, which call for equal opportunities and fair treatment for all business actors.Therefore, stricter oversight from competition authorities and regulatory evaluation are needed to ensure fair, healthy competition that aligns with both legal norms and Islamic economic values. This research is expected to contribute to strengthening digital business competition policies based on the values of Sharia justice